2004
DOI: 10.1097/01.phm.0000130026.12790.20
|View full text |Cite
|
Sign up to set email alerts
|

Structured Nursing Intervention Versus Routine Rehabilitation After Stroke

Abstract: The nursing intervention had both short- and long-term effects on functional, psychological, and emotional variables. Serious consideration should be given to implementing comprehensive nursing interventions during rehabilitation tailored to meet the specific needs of stroke survivors and their caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 20 publications
2
49
1
Order By: Relevance
“…16 Although therapists support functional recovery, 2 nurses and SW play an important role in identifying social and emotional challenges and supporting patients as they recover from stroke. [17][18][19] Social care has been identified as a particular challenge in securing timely discharge to ESD, 20 which further highlights the importance of the inclusion of nurses and social workers in interprofessional ESD teams. Based on the results of this review, it would be our recommendation that PT, OT, SLP, SW, and nursing be considered as critical components of an effective ESD team.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although therapists support functional recovery, 2 nurses and SW play an important role in identifying social and emotional challenges and supporting patients as they recover from stroke. [17][18][19] Social care has been identified as a particular challenge in securing timely discharge to ESD, 20 which further highlights the importance of the inclusion of nurses and social workers in interprofessional ESD teams. Based on the results of this review, it would be our recommendation that PT, OT, SLP, SW, and nursing be considered as critical components of an effective ESD team.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies each reported on more than one stroke risk factor, nine interventions had a focus on self-management for lifestyle behaviours in general [31-35, 38-40, 43], two interventions had a specific focus on self-management for physical activity [42][43][44], two interventions had a focus on blood pressure [36,41], and one on medication adherence [37].…”
Section: Resultsmentioning
confidence: 99%
“…In seven studies, the interventions were administered in-person [32, 34, 36-37, 40, 43-44], six on an individual basis [34, 36-37, [43][44][45], one using a group format [32], and one using both individual and group formats [40]. Three studies delivered the intervention via telehealth, using a telephone [33,38] [41][42]).…”
Section: Resultsmentioning
confidence: 99%
“…Assessing individual needs, responding to patients as individuals and engaging with those close to them may be especially difficult when patients are unable to engage in normal social interactions and about whom nursing staff may have little or no prior knowledge (Rogers & Addington-Hall 2005). Such patients are easily forgotten in busy acute environments, where the focus of specialist stroke care tends to be on rehabilitation and recovery (Coleman Gross et al 2001, Hilderley et al 2002, Nir et al 2004.…”
Section: Stroke Care At the End Of Lifementioning
confidence: 99%